Reading as a way to access the world of fantasy and creativity - Rangel Ramos, Ana Milena; Acevedo Rodriguez, María Paola; Aparicio, Silvia Margarita (Rastros Rostros, 2024)
This article is part of the formative research process carried out with the second grade A group of the San Cristobal School concentration, with Carmenza Aparicip Jaimes as the head teacher. In this space, an initial diagnostic observation was made, in which it was possible to corroborate that the lack of motivation and aversion to reading is due to the lack of didactic tools and texts that the children like.